2008
DOI: 10.3844/ajassp.2008.203.208
|View full text |Cite
|
Sign up to set email alerts
|

Political Stability and Economic Growth in Asia

Abstract: This study investigates the effects of various factors of political instability on economic growth in selected ten Asian economies during 1990-2005. Our empirical findings show a close relationship between political stability and economic growth. We have analyzed the data by using ordinary least squire econometrics methods, which conclude that 32.35 scores increasing of index of political stability leads to one percent increase in economic growth. From these finding based on Asia experiences, we can conjecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 8 publications
0
33
0
2
Order By: Relevance
“…However, found political stability as negatively effecting FDI inflows. Apart from this that; political stability adds to economic wellbeing (GDP growth), as found by Younis et al (2008), mixed results are found while looking for effects of political stability towards FDI inflows 3 .…”
Section: Long-run Coefficientsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, found political stability as negatively effecting FDI inflows. Apart from this that; political stability adds to economic wellbeing (GDP growth), as found by Younis et al (2008), mixed results are found while looking for effects of political stability towards FDI inflows 3 .…”
Section: Long-run Coefficientsmentioning
confidence: 92%
“…In case of Asian Economies, political stability stands as vital in its role for economic growth. Its effects are transformed to economic growth of a particular country in response to accumulation of capital, in terms of human capital, and foreign capital inflows, such as FDI (Younis, Lin, & Sharahili, 2008).…”
Section: Fdi and Political Stabilitymentioning
confidence: 99%
“…2 In this paper, we intend to quantify the role of optimistic economic expectations in keeping the Chinese happy, amidst all the social and economic 1 Examples of this idea from public think-tanks and political scientists include Holbig (2006), Giessmann (2007), and Zeng (2003). 2 Younis et al (2008), looking at the di¤erential growth experience across South Asian countries in the past few decades, indeed also suggest that political stability and economic growth go hand in hand, though they cannot ascertain the main direction of causality. 1 changes.…”
Section: Introductionmentioning
confidence: 99%
“…The index for political stability is obtained from previous study [10] . Index for political stability covers nine variables, which are longevity of the regime, Election density ratio, Increase in the number of political parties, Strength of ruling party, Military expenditure as a percentage of GDP, Index of democratization, Composite of ICRG risk rating, Numbers of persons internally displaced and Increment of political parities in national assembly.…”
Section: Methodsmentioning
confidence: 99%
“…The data on balance of payment is taken from world development report [10] . Table in Gross international reserves and exchange rate stability are indicators of nature of overall balance of payment.…”
Section: Methodsmentioning
confidence: 99%